Fourth-order elliptic problems with critical nonlinearities by a sublinear perturbation - Li, Lin; O’Regan, Donal (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we get the existence of two positive solutions for a fourth-order problem with Navier boundary condition. Our nonlinearity has a critical growth, and the method is a local minimum theorem obtained by Bonanno.
Keywords: critical growth; biharmonic operator; variational methods; local minimum